Exercise promotes positive impression formation towards both men and women - Kanarek, Robin B.; Mathes, Wendy Foulds; D’Anci, Kristen E. (Appetite, 2012)
Exercise is endorsed for its physiological and psychological benefits, and has been proposed to have positive effects on impression formation. To test this proposal, 62 female and 44 male college students read one of three brief descriptions of either a fictitious male or female “target” student. The descriptions varied only in exercise level: no exercise; moderate exercise and intensive exercise. Participants then rated the fictitious student on 38 personality traits. Ratings of characteristics that are associated with exercise (e.g. athletic; energetic) increased, while ratings associated with the lack of exercise (e.g. lazy; weak) decreased as a function of the reported level of exercise. Exercise level also positively influenced ratings of characteristics not related to exercise. These data show that even minimal information about exercise is an important component of first impressions in both men and women.